Las Zwierzyniecki as an Element of the Composition of Green Areas in Białystok - Gawryluk, Dorota (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2019)
The article presents a historical and compositional analysis of the changes done to “Las Zwierzyniecki”[1] (now a public park and nature reserve) in Białystok. It describes the stages of its transformation in the context of the changes done to the baroque composition of the Branicki residence and menageries from the 18th to early 21st century. An attempt was made to describe the historical and compositional design guidelines for the modern revitalisation of Las Zwierzyniecki. [1] Roughly translatable as the Zwierzyniec (menagerie) Forest